Types and outcomes of safety interventions addressed to diverse workers: A scoping review - Di Marco, D.; Corlett, S.; Silva, S. da.; Paolillo, A. (Safety Science, 2026)
The goal of this scoping review is to map the types and outcomes of interventions aimed at increasing safety and reducing workplace hazards of diverse workers. After searching Web of Science, Scopus and PsycInfo, 23 papers addressing safety interventions for diverse workers were selected. We extracted and systematized the data by filling in a form with specific information about each study. The included studies were published between 2003 and 2023. They were mainly conducted in the United States, followed by Australia, Bangladesh, Canada, Gambia, India, Qatar, and South Africa. Most of the interventions targeted immigrant and ethnic minority groups, followed by young and/or older workers, women, mixed groups (women and young/older workers) and workers from low-wage countries. Different strategies were applied to adapt the interventions to the specific needs of the diverse workers (e.g., language and cultural adaptation, provision of different stimuli during the training according to the participants’ age). The intervention outcomes were measured in several ways, for instance, in terms of knowledge acquisition and transfer, hazard identification and reduction, and improvements in safety behaviors. The findings showed that safety interventions are more effective when tailored to the specific needs of diverse workers. In many cases, interventions yielded more positive results when trainers from the target group were involved. These findings can guide the design of future safety interventions, and should encourage future research to extend to other diverse workers (e.g., people with disability and LGBTQ workers), by considering their unique characteristics and needs.